1985
DOI: 10.1056/nejm198504043121403
|View full text |Cite
|
Sign up to set email alerts
|

Hematologically and Genetically Distinct Forms of Sickle Cell Anemia in Africa

Abstract: Patients with sickle cell anemia vary in the hematologic and clinical features of their disease, in part because of variability in the presence of linked and unlinked genes that modify the expression of the disease. The hemoglobin S gene is strongly linked to three different haplotypes of polymorphic endonuclease-restriction sites of the beta-like gene cluster (genes in the vicinity of the beta-globin gene)--one prevalent in Atlantic West Africa, another in central West Africa, and yet another in Bantu-speakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
3
8

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 22 publications
9
129
3
8
Order By: Relevance
“…The absence of a strong effect for a-thalassemia in SCD pulmonary hypertension was unexpected in contrast to the findings with Hb SC, despite the increased statistical power from the presence of the a 3.7 allele at nearly three times the frequency of Hb C. Still, the magnitude of a 3.7 's effect may be sufficiently small to be below the threshold for detection for the statistical power in this study. Likewise, haplotypes of the b-globin locus have been used in the past to study both the variation in SCD severity and the evolutionary history of the b S mutation [47][48][49][50]27]. In particular, some of the variability in Hb F expression is attributable to functional alleles in the fetal hemoglobin genes inherited on specific b S -globin haplotypes [48,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a strong effect for a-thalassemia in SCD pulmonary hypertension was unexpected in contrast to the findings with Hb SC, despite the increased statistical power from the presence of the a 3.7 allele at nearly three times the frequency of Hb C. Still, the magnitude of a 3.7 's effect may be sufficiently small to be below the threshold for detection for the statistical power in this study. Likewise, haplotypes of the b-globin locus have been used in the past to study both the variation in SCD severity and the evolutionary history of the b S mutation [47][48][49][50]27]. In particular, some of the variability in Hb F expression is attributable to functional alleles in the fetal hemoglobin genes inherited on specific b S -globin haplotypes [48,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, haplotypes of the b-globin locus have been used in the past to study both the variation in SCD severity and the evolutionary history of the b S mutation [47][48][49][50]27]. In particular, some of the variability in Hb F expression is attributable to functional alleles in the fetal hemoglobin genes inherited on specific b S -globin haplotypes [48,[51][52][53]. Fetal hemoglobin expression may be relevant to pulmonary hypertension, as this and other studies have observed significantly lower levels of Hb F in SCD pulmonary hypertension cases (Table IV) [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The non-Black African SCA variant manifests with a less severe phenotype than the Black African variant. [6][7][8] Children with Black African variant SCA were prone to invasive infections caused by Streptococcus pneumonia, Haemophilus influenzae and Plasmodium falciparum (in malaria areas). Malaria is more endemic in Black African areas and therefore malaria is more common in black SCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the Black African SCA variant manifest a more severe form of SCA than patients with the non-Black African variant. [6][7][8] For patients with the Black African variant, painful crises, chest syndrome and stroke are more frequent and appear earlier in life, while patients with the nonblack African variant are more likely to become dependent on RBC transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the DNA structure flanking the b-globin locus of HbS suggests that the mutation has arisen on at least three independent occasions in the African continent, referred to as b-globin haplotypes and named after the areas where they were first described: Benin, Senegal, and Central African Republic or Bantu (Pagnier et al 1984;Nagel et al 1985;Chebloune et al 1988). The HbC trait is believed to be a relatively recent mutation limited to West Africa where it occurs at high frequencies (.20%) in central Ghana and Burkina Faso, in only 2% in Nigeria, and does not occur, except in peoples of West African origin, in East and Central Africa.…”
Section: Geography Of Sickle Cell Disease Populations Of African Originmentioning
confidence: 99%